Léopold Sédar Senghor pri Slovencih - Smolej, Tone (Ars et humanitas, 2009)
Although Senghor has been known in Slovenia since the 1950s, he only became known to the general public in the first half of the 1970s, when Aleš Berger began to translate his work. Senghor's visit to Slovenia in the summer of 1975 was undoubtedly a factor in the publication of a selection of his poems in the prestigious collection Lirika. This study shows that the Slovenian translator offers apposite translations of Senghor's images and that he Slovenianized certain of Senghor's words of African origin. The Slovenian colection of Senghor's poems also reveals some editorial mistakes because part of his Songs for Signare has been appended to Black Woman and to New York in the Slovene edition, which somewhat hinders the reading of the poems.
Keywords: Senghor, Léopold Sédar, 1906-2001; afriške književnosti; senegalska književnost; prevajanje; translation